NORMS, NORMATIVE UTTERANCES, AND NORMATIVE PROPOSITIONS - RISTO HILPINEN (Análisis Filosófico, 2006)
It is argued that the distinction between the normative and the descriptive interpretation of norm sentences can be regarded as a distinction between two kinds of utterances. A norm or a directive has as its content a normative proposition. A normative (performative) utterance of a normative proposition in appropriate circumstances makes the proposition true, and an assertive (descriptive) utterance has as its truth-maker the norm system to which it refers. This account of norms, norm-contents, and utterances of norm sentences solves Jørgensen’s problem: logical relations among norms can be defined in the usual way in terms of the truth-conditions of the normative propo- sitions which form their content. There is no distinction between the logic of norms and the logic of normative propositions; in this respect the present account differs from Carlos Alchourrón and Eugenio Bulygin’s account of the logic of normative propositions.